Theoretical study of the electronic and optical properties of a composite formed by the zeolite NaA and a magnetite cluster - Joel Antúnez-García; Roberto Núñez-González; Vitalii Petranovskii; H’Linh Hmok; Armando Reyes-Serrato; Fabian N. Murrieta-Rico; Mufei Xiao; Jonathan Zamora (Beilstein Journal of Nanotechnology)
The electronic and optical properties of a composite created by introducing a magnetite cluster into NaA zeolite have been investigated in this work using DFT calculations. The results obtained indicate that the electronic and optical properties of the composite are enhanced because of the cluster. However, the properties exhibited by the cluster outside the zeolite differ from those it presents when it is part of the composite. It is noteworthy that the composite exhibits magnetic properties of a half-semiconductor and a strong optical response within the visible and ultraviolet regions of the spectrum.